Benchmarking Structural Change in Transition - Martin Raiser; Mark E. Schaffer; Johannes Schuchhardt (Institute for the Study of Labor (IZA), 2003)
The transition to market-based economic systems in the countries of Central and Eastern Europe and the former Soviet Union involves fundamental shifts in the allocation of resources and deep changes in the structure of production and employment. This paper uses a simple model of economic development and structural change with technology spillovers to benchmark structural change in the transition economies and simulate the path of adjustment from central planning. We then analyse data from 10 accession candidates and 12 CIS countries to measure the progress in structural change that has taken place thus far and to assess the further structural changes that should be expected, with particular attention to the implications for accession.
Keywords: O14; P20; O40; 330; structural change; transition; adjustment; Übergangswirtschaft; Strukturwandel; Benchmarking; EU-Erweiterung; Drei-Sektoren-Hypothese; Schätzung; Osteuropa; GUS